Patih Bersidig Cartu Tingkatkan Kompetensi Guru Mata Pelajaran IPA di Era Revolusi Industri 4.0 - Lilik Rahmawati (Jurnal Pengabdian KOLABORATIF, 2023)
The condition of most science teachers in the Grobogan District has not been optimal in utilizing digital technology in the learning process. Training is a form of activity chosen by the school superintendent to guide science teachers in Grobogan in collaboration with subject-teacher deliberations (MGMP). The purpose of this best practice is to describe the implementation, results, and impact of digital-based training are a surefire way "Patih Bersidig Cartu" to improve the competence of natural science teachers in the era of the industrial revolution 4.0. The delivery of training materials is carried out using the blended learning method, namely face-to-face and online. In addition to receiving material, participants also work on assignments through google classroom. The results of Patih Bersidig Cartu to improve the competence of natural science teachers in the era of the industrial revolution 4.0 including teachers can make presentation media in the form of videos; teachers can create interactive learning media with classpoints; teachers can create online learner worksheets (LKPD), learning poster media, learning infographic media, learning comics, presentation media, and digital books, learning videos by utilizing canva for education in natural science materials in grades 7, 8, and 9.